1996
DOI: 10.1002/(sici)1098-2361(1996)15:4<383::aid-zoo3>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral effects of changing group membership among captive lowland gorillas

Abstract: Group membership was modified among 4 gorilla groups at Zoo Atlanta in an attempt to increase compatibility and sexual behavior. The modifications ultimately moved 7 adult females among the groups. The moves were made by individually introducing the new group members to the old members, resulting in 18 total introductions. Several individual and social behaviors differed in the two conditions. The most obvious change was a temporary increase in aggressive display behaviors, as well as an increase in contact an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Two proximity categories were used in the analyses: within 1 m, and within 1-5 m. The ''within 1 m'' category included animals that were in contact or within arm's reach of each other, while the ''within 1-5 m'' category included animals that were out of arm's reach but within visual vigilance levels. We focused on proximity patterns because of the infrequent occurrence of social interactions among gorillas [Harcourt, 1979a;Watts, 1992Watts, , 1994Hoff et al, 1996]. Studies of wild mountain gorillas have shown that proximity is an accurate indicator of social relationships [Watts, 1994].…”
Section: Methodsmentioning
confidence: 99%
“…Two proximity categories were used in the analyses: within 1 m, and within 1-5 m. The ''within 1 m'' category included animals that were in contact or within arm's reach of each other, while the ''within 1-5 m'' category included animals that were out of arm's reach but within visual vigilance levels. We focused on proximity patterns because of the infrequent occurrence of social interactions among gorillas [Harcourt, 1979a;Watts, 1992Watts, , 1994Hoff et al, 1996]. Studies of wild mountain gorillas have shown that proximity is an accurate indicator of social relationships [Watts, 1994].…”
Section: Methodsmentioning
confidence: 99%
“…In 1988 two 99 and a silverback, all wild-born, were transferred with a number of other gorillas to the Zoo from Yerkes Regional Primate Research Center, Atlanta, following the construction of four naturalistic habitats (Ogden et al, 1990). Two juvenile 66 in this group were born at the Zoo: one was 5years and 5 months old when the silverback died and his mother had been moved to another group 2 years previously (Hoff et al, 1996); the other was 3 years and 7 months old when the silverback died and was still housed with his mother. The study group comprised a silverback 8, three adult 99 and two juvenile 88 (Table 1).…”
Section: Subjectsmentioning
confidence: 99%
“…PROCEDURE Data were collected over a 6 month period. Because the group was part of a larger study of gorilla adaptation to a new environment (Ogden et al, 1990;Hoff et al, 1994Hoff et al, , 1996Hoff & Maple, 1995) and was being studied systematically with the other groups at the Zoo, data for the 3 months prior to the death of the 6 could be compared with data for the 3 months following his death.…”
Section: Housing and Feedingmentioning
confidence: 99%
“…However, in captivity, a group could lose a silverback because that individual has been transferred to another zoo or because that individual has died. Hoff et al [1996] documented the effect of moving females between groups, but did not examine the effect of removing a male for husbandry purposes. Two articles have documented captive gorilla responses to death of a silverback male; both have focused on singlemale groups.…”
Section: Introductionmentioning
confidence: 99%